A PERANAN BLENDED LEARNING TERHADAP EVALUASI PEMBELAJARAAN TEMATIK DI SEKOLAH DASAR: Analisis Deskriptif - Maulana, Reza; Lestari, Wahyu (STKIP Subang, 2021)
The purpose of this study is to analyze the role of Blended Learning learning program to evaluate thematic learning in thematic elementary school in terms of context, input, process, SD Insan Kamil Bogor. This type of research is descriptive with a qualitative approach. The subjects of this study were principals, grade IV teachers, and grade IV students. Data collection techniques using interviews, observations, questionnaires, and documentation. The assessment criteria as the evaluation benchmark in this study refers to the reference that has been made. The results showed that (1) the thematic learning context component in Insan Kamil Bogor based on the results of interviews with principals and teachers fall into the good category. Learning objectives that are in accordance with the analysis of needs but tend not to be implemented consequently in the thematic learning process because the teacher does not understand the background and the importance of the implementation of thematic learning programs for students in the early grades; (2) the input components of syllabus and RPP aspects, learning facilities, and learning motivation in general are in the excellent category; (3) the process component of the teacher performance aspect in the classroom in general falls into the category of less because so far the teacher has not been maximal in teaching thematic and is more likely to teach the subjects only. It is recommended to teachers and policy makers to be able to conduct innovative evaluations and activities so that thematic learning programs can run as much as possible.